Advances in Organic Synthesis on Ionic Liquid Platforms: An Account of Indian Research Contributions - Handique, Prapti Priyam; Paul, Subham; Dutta, Papia; Gogoi, Pinky; Morang, Jita; Dutta, Minmoy; Borah, Ruli (Synlett, 2025)
The exploration of ionic liquids, with their unique physicochemical and task specific properties, has made notable progress in organic synthesis highlighting their use as sustainable catalysts/solvents/bifunctional solvent-catalytic systems. This account presents a comprehensive survey of the development of sustainable organic synthesis using ionic liquid materials in India since 2000. The tunability of the properties of ionic liquids with their structural diversity is discussed together with the classification of ionic liquids material according to different aspects. The applications of ionic liquids are extensively review for a wide array of organic reactions, such as nucleophilic addition, elimination reactions, conjugate addition reactions, condensation, protection of functional groups, esterification, pericyclic reactions, coupling reactions, heterocycle synthesis, and miscellaneous reactions.1 Introduction2 Classification of Ionic Liquids2.1 Based on Structure and Physicochemical Properties2.2 Based on Reactivity of the Ionic Liquid2.3 Based on the Number of Cations in the Ionic Liquid2.4 Based on Functionality3 Applications of Ionic Liquid Systems in Organic Synthesis3.1 Nucleophilic Substitution3.2 Elimination Reactions3.3 Conjugate Addition Reactions3.4 Condensation Reactions3.5 Protection of Functional Groups3.6 Esterification3.7 Pericyclic Reactions3.8 Coupling Reactions3.9 Synthesis of Heterocycles3.10 Miscellaneous Reactions3.10.1 Nucleophilic Addition Reactions3.10.2 Electrophilic Aromatic Substitution3.10.3 Reductive Amination3.10.4 Decarboxylation Reactions3.10.5 Carbonylation Reactions3.10.6 Rearrangement Reactions3.10.7 Oxidation4 Conclusion
Keywords: ionic liquids; organic synthesis; catalysis; solvent-catalyst; recyclable